If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-6v + 6) + -1v = 2(v + -8) + -7 Reorder the terms: -3(6 + -6v) + -1v = 2(v + -8) + -7 (6 * -3 + -6v * -3) + -1v = 2(v + -8) + -7 (-18 + 18v) + -1v = 2(v + -8) + -7 Combine like terms: 18v + -1v = 17v -18 + 17v = 2(v + -8) + -7 Reorder the terms: -18 + 17v = 2(-8 + v) + -7 -18 + 17v = (-8 * 2 + v * 2) + -7 -18 + 17v = (-16 + 2v) + -7 Reorder the terms: -18 + 17v = -16 + -7 + 2v Combine like terms: -16 + -7 = -23 -18 + 17v = -23 + 2v Solving -18 + 17v = -23 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. -18 + 17v + -2v = -23 + 2v + -2v Combine like terms: 17v + -2v = 15v -18 + 15v = -23 + 2v + -2v Combine like terms: 2v + -2v = 0 -18 + 15v = -23 + 0 -18 + 15v = -23 Add '18' to each side of the equation. -18 + 18 + 15v = -23 + 18 Combine like terms: -18 + 18 = 0 0 + 15v = -23 + 18 15v = -23 + 18 Combine like terms: -23 + 18 = -5 15v = -5 Divide each side by '15'. v = -0.3333333333 Simplifying v = -0.3333333333
| -5/8x-7.5=7.5 | | -5y=6-4y | | 12(n+1)+-11n+2(n+1)=56 | | 7-3(19z-17)=-4(-2z+18) | | 2g=3g-9 | | -5/8x=0 | | -15+3(b+2)+4(b+1)=2 | | 7h+2=8h-6 | | -9+8b=-b | | 9h-7=3+7h | | h=-16t^2+38t+15 | | 3.7+13.4h=12.94+14.1h | | x/10=10*x | | 2cos(3x)= | | 8x^3-126x-4=0 | | 4(y+6)=-2(4y-9)+2y | | 4(y-5)=44 | | -41-1[2+5y-9(y+2)]=-5(2y-5)-[7(y-1)-3y+3] | | 6t=7t+4 | | -5/6x=7 | | -5.94+2.6q=3.7q | | -10-11x-24=3x | | -7(w-1)=-3w-9 | | -2r=-7-r | | -9+6b=-b | | w-10=8.1 | | 5x-2y+7z=12 | | -3.9y=-1.86-4y | | 10-3c=-2c | | 8-6d=2-5d | | 3(p+4)+-4p+8(p+1)=90 | | -7x-18=8(x-6) |